LEGAL PROTECTION OF PAPUAN INDIGENOUS PEOPLES THROUGH THE ROLE OF THE PAPUAN PEOPLE'S ASSEMBLY REGARDING FOREIGN INVESTMENT AFTER THE PAPUA SPECIAL AUTONOMY LAW - Filep Wamafma (Awang Long Law Review, 2026)
One of Papua's special autonomy rights is the existence of the Papuan People's Council (MRP) as a cultural representation of the indigenous Papuan population which is given certain powers. The main problem is that the MRP, which is a direct representative of indigenous Papuans, is considered to have weak authority in carrying out the direct aspirations of the Indigenous Papuan people, including matters relating to the entry of foreign investors into their customary land. Therefore, the implications of foreign investment on the enjoyment and ownership of indigenous peoples' rights to land are becoming increasingly neglected. This research was conducted to examine the legal protection of Papua's indigenous communities through the role of the Papuan People's Council towards foreign investment. This type of research is included in normative juridical with a statutory approach. The research results show that the regulation of foreign investment in Indonesia is regulated by Law Number 25 of 2007. This law contains a number of principles which form the background for the formation of norms and rules contained in the articles of this law. The legal protection of Papua's indigenous communities in relation to foreign investment is realized through several provisions, including Article 38 paragraph (2) and Article 43 of Law Number 21 of 2001 concerning Special Autonomy for Papua Province. In this law, it is stipulated that economic businesses that utilize natural resources in Papua must respect the rights of indigenous peoples. Furthermore, the Papuan People's Assembly must pay attention to indigenous communities in carrying out its functions and authority.